The effect of pre-exercise protein intake on substrate metabolism, energy expenditure, and energy intake: a dose-response study - Wouter Michiel Peeters; Lauren Elizabetha Cook; Oliver Page (Taylor & Francis Group, 2023)
ABSTRACTBackground Pre-exercise protein consumption does not seem to influence substrate metabolism during exercise compared to fasted exercise, however it is unclear if the protein dose impacts on this effect.Methods In a randomized, double-blinded within-subject design trial, healthy, active males and females (n = 15, 25 ± 5 yrs, O2peak: 47.5 ± 8.8 ml/kg/min) completed 1 h of cycling exercise at 60% peak power output 30 min after having consumed either 0, 20, or 40 g of whey protein. Indirect calorimetry was used to measure substrate oxidation during exercise and baseline and post-exercise resting energy expenditure. Blood samples were taken throughout the trials to measure metabolic responses. Free-living food intake post-trial was collected using food diaries.Results Fat oxidation rates during exercise did not differ between the three conditions (p = 0.19) with small effect sizes between conditions (Cohen's dz: 0 vs. 20 g = 0.22, 0 vs. 40 g = 0.47, 20 vs. 40 g = 0.27). Serum insulin was higher in the protein groups vs. 0 g (p < 0.05), whereas non-esterified fatty acids were higher in the 0 g compared to 20 and 40 g (p < 0.05). Glucose was significantly lower after 15 min of exercise in 20 and 40 g vs. 0 g (p = 0.01). Resting energy expenditure was elevated post-exercise (p < 0.001), without an interaction for protein dose (p = 0.90). Post-trial free-living energy intake was not different between conditions (p = 0.31), but 24-h energy intake was significantly higher in 40 vs. 0 g (p = 0.04).Conclusion Protein doses up to 40 g do not seem to impair fat oxidation rates during exercise compared to fasted exercise and could be considered as a nutritional strategy for exercising individuals who struggle to include fasted exercise in their training.